Respiratory health of young shipyard welders and other tradesmen studied cross sectionally and longitudinally. - Chinn, D J (1995)
OBJECTIVE--To assess the effectiveness of current measures for protecting shipyard welders and caulker/burners (WCBs) from the respiratory effects of fumes. METHODS--Shipyard tradesmen born after 1953 (cohort 1), and 181 older men, subjects of a previous study (cohort 2), were assessed, then followed up after an average interval of 6.7 years. The respiratory associations with shipyard trades were assessed cross sectionally and longitudinally and an estimate made of the likely effects of selection bias. Cohort 1 comprised 90% of the 462 eligible WCBs and 239 other tradesmen; there were 31 exclusions. At follow up 139 of 146 men still in the shipyard and 43% of those who had left were reassessed. The lapses were mainly due to migration. All members of cohort 2 were followed up for respiratory symptoms (from MRC questionnaire), were recorded, and indices reflecting all aspects of lung function were measured. RESULTS--At the initial assessment and independent of smoking, trade as a WCB was associated with increased prevalences of chronic cough, phlegm, and wheeze, a reduced transfer factor, and an enhanced age related deterioration in peak expiratory flow (measured cross sectionally). Continued work as a WCB was associated with enhanced deterioration in lung function despite some amelioration of respiratory symptoms; the deterioration was influenced by whether or not exhaust ventilation had been used for every weld. The effects of fume on forced expiratory volume, flow-volume curvilinearity, mean transit time, and moment ratio were independent of and at least as large as those due to smoking. Enhanced deterioration in peak expiratory flow was confined to WCBs who smoked. These effects of trade, but not those of smoking, were nearly independent of atopy. CONCLUSION--In WCBs the working practices over the period of the study did not prevent the development of mild respiratory impairment. In WCBs who used exhaust ventilation at all times, the impairment seemed to reverse by discontinuation of exposure. Thus existing hygiene measures should be applied rigorously. The biological effectiveness of these and any other necessary supplementary measures should be assessed by long term monitoring of forced expiratory volume and peak expiratory flow.